Climate Change Will Impact Surface Water Extents and Dynamics Across the Central United States - Vanderhoof, Melanie K.; Christensen, Jay R.; Alexander, Laurie C.; Lane, Charles R.; Golden, Heather E. (Earth's future, 2024)
Climate change is projected to impact river, lake, and wetland hydrology, with global implications for the condition and productivity of aquatic ecosystems. We integrated Sentinel‐1 and Sentinel‐2 based algorithms to track monthly surface water extent (2017–2021) for 32 sites across the central United States (U.S.). Median surface water extent was highly variable across sites, ranging from 3.9% to 45.1% of a site. To account for landscape‐based differences (e.g., water storage capacity, land use) in the response of surface water extents to meteorological conditions, individual statistical models were developed for each site. Future changes to climate were defined as the difference between 2006–2025 and 2061–2080 using MACA‐CMIP5 (MACAv2‐METDATA) Global Circulation Models. Time series of climate change adjusted surface water extents were projected. Annually, 19 of the 32 sites under RCP4.5 and 22 of the 32 sites under RCP8.5 were projected to show an average decline in surface water extent, with drying most consistent across the southeast central, southwest central, and midwest central U.S. Projected declines under surface water dry conditions at these sites suggest greater impacts of drought events are likely in the future. Projected changes were seasonally variable, with the greatest decline in surface water extent expected in summer and fall seasons. In contrast, many north central sites showed a projected increase in surface water in most seasons, relative to the 2017–2021 period, likely attributable to projected increases in winter and spring precipitation exceeding increases in projected temperature. Plain Language Summary Climate change is expected to impact rivers, lakes, and wetlands. In this effort we used multiple satellites to track monthly surface water extent (2017–2021) for 32 sites across the central United States. The average amount of surface water was highly variable across sites. Individual statistical models, relating meteorological variables to surface water extent, were developed for each site. The models were then updated with climate change adjusted variables. Most sites were projected to show a decline in surface water extent, with drying most consistent across the southeast central, southwest central, and midwest central U.S. Projected declines under dry conditions at these sites suggest greater impacts of drought events are likely. Projected changes were seasonally variable, with the greatest decline in surface water extent expected in summer and fall seasons. In contrast, many north central sites showed a projected increase in surface water in most seasons, likely attributable to projected increases in winter and spring precipitation. Key Points Surface water across the central U.S. responds to episodic, seasonal, and interannual variability in water availability Most sites showed projected declines in surface water extents under RCP4.5 and 8.5, peaking in summer‐fall and increasing drought impacts Select sites, concentrated in the north central U.S., projected increases in surface water, associated with greater precipitation